Crushing behaviour of glass fibre/epoxy composite pipes: The effects of winding angles, ageing, and temperatures - Nurul Fitriah Suhaimi (School of Mechatronic Engineering, 2016)
The research objectives are to investigate the crushing failure of glass fiber reinforced epoxy (GRE) composite pipes of various winding angles; to investigate the effects of elevated temperature and ageing on the crushing behaviour of GRE composite pipes; to model of compressive behaviour of GRE pipes and comparison with experimental findings.